Studio television production and directing - Utterback, Andrew Hicks (Amsterdam ; Boston : Focal Press, 2007)
"Learn how to direct television programs, understand complex directing tasks, and grasp the fundamentals of television production procedure in this back-to-basics guide to studio-based production. Lighting, set, camera operations, floor direction, technical direction, audio, tape, graphics, prompting, and assistant directing are covered individually and from the director's point of view. The live, affiliate-level newscast is used as the running example to illuminate television production and control room procedures for your newscast or other program genre. You'll soon be able to direct any type of studio-based program with ease." "Heavily illustrated and designed as a quick reference for on set, this guide is essential for studio television production students and aspiring directors. Includes a glossary of the director's command cue language and a detailed production vocabulary."--BOOK JACKET.
Overview of equipment and positions : the studio and the control room -- Audio control and technical directing -- Lighting and sets -- Studio cameras and floor directing -- Prompter, graphics, tape -- Rundowns, scripts, video clip information -- Assistant directing and directing.
Includes index.
Keywords: Television -- Production and direction